Fighting terrorism in Africa: evidence from bundling and unbundling institutions - Simplice Asongu; Vanessa Tchamyou; Ndemaze Asongu; Nina Tchamyou (African Governance and Development Institute (AGDI), 2017)
This study assesses government mechanisms in the fight against terrorism with particular emphasis on the bundling and unbundling of ten governance dynamics. The empirical evidence is based on a panel of 53 African countries for period 1998-2012 and Generalized Method of Moments. The following findings are established. First, for the most part, political governance and its constituents respectively have negative effects on all terrorism dynamics, with the following consistent increasing order of negative magnitude: unclear terrorism, transnational terrorism, domestic terrorism and total terrorism. Second, overwhelmingly for economic and institutional governances, the governance dynamics and their constituent components affect terrorism negatively, with the magnitude on domestic terrorism consistently higher than that on transnational terrorism. Third, for most specifications, the effect of general governance is consistently negative on terrorism variables. Theoretical and practical policy implications are discussed.
Keywords: C52; D74; F42; O38; P37; 330; Terrorism; Common policies; governance; Africa